The geopolitical location of Slovenia in the perspective of European integration processes - Bufon, Milan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
The paper will briefly present some basic political geographical features of Slovenia, particularely for what regards its "border" position from a geopolitical perspective. The most evident result of the most recent geopolitical transformations is represented by a general geopolitical re-orientation of the country towards north and west, a changing territorial affiliation and mediation role, which before 1991 appeared to be oriented fromthe Balkans towards Central and Western Europe, and has after that turned from Central and Western Europe towards the Balkans. The paper also aims to give an analysis of the various border and contact areas in Slovenia.
Keywords: Europe; Evropa; geopolitika; integracija; integracijski procesi; mednarodne integracije; obmejna območja; obmejno sodelovanje; politična geografija; regije; Slovenia; Slovenija